2016
DOI: 10.1111/ijlh.12613
|View full text |Cite
|
Sign up to set email alerts
|

Spur cell anemia in Wilson's disease: a rare presentation

Abstract: A 9-year-old girl presented to our outpatient department with fever, yellowish discoloration of sclera, and abdominal distension since one-and-a-half month. There was no significant past or family history. Pallor, icterus, ascites, and dilated veins over the abdomen were present on examination. Liver function test showed increased total and direct bilirubin 13.8 mg/dL (0.3-1.2 mg/dL) and 8.4 mg/dL (0.1-0.2 mg/dL), hypoalbuminemia (total protein : 40 g/L (64-81 g/L); albumin: 20 g/L (35-50 g/L)), and deranged c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Vassiliadis et al reported a 25-day median survival rate in the 9 patients with SCA, and only one patient, who had undergone liver transplantation, had survived after 1 year [12]. To our knowledge, there have been 24 case reports on 26 patients with SCA since 1983 including our case (Table 3) [13,14,16,19,20,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. On reviewing these cases, the average age was 42.6 years old, and 14 (53.8%) of the 26 patients were men.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Vassiliadis et al reported a 25-day median survival rate in the 9 patients with SCA, and only one patient, who had undergone liver transplantation, had survived after 1 year [12]. To our knowledge, there have been 24 case reports on 26 patients with SCA since 1983 including our case (Table 3) [13,14,16,19,20,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. On reviewing these cases, the average age was 42.6 years old, and 14 (53.8%) of the 26 patients were men.…”
Section: Discussionmentioning
confidence: 66%
“…SCA was originally reported as a severe form of hemolytic anemia, with the presence of spur cells on a peripheral blood smear [9]. Recently, various etiologies of liver cirrhosis were reported as causes of SCA, which is shown to occur in any etiology of liver cirrhosis [19][20][21]. The precise mechanism of SCA in liver cirrhosis is still unknown, although abnormal ratio of cholesterol and phospholipids in red blood cell membrane is thought to be the main cause of SCA [9,15].…”
Section: Discussionmentioning
confidence: 99%